2015
DOI: 10.1093/mnras/stu2758
|View full text |Cite
|
Sign up to set email alerts
|

Modelling grain alignment by radiative torques and hydrogen formation torques in reflection nebula

Abstract: Reflection nebulae-dense cores-illuminated by surrounding stars offer a unique opportunity to directly test our quantitative model of grain alignment based on radiative torques (RATs) and to explore new effects arising from additional torques. In this paper, we first perform detailed modeling of grain alignment by RATs for the IC 63 reflection nebula illuminated both by a nearby γ Cas star and the diffuse interstellar radiation field. We calculate linear polarization p λ of background stars by radiatively alig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 63 publications
4
44
0
Order By: Relevance
“…Hoang & Lazarian (2009b) found that RAT alignment is shown to be enhanced by pinwheel torques. The effect of alignment by H 2 torques is observed in reflection nebula IC 63 (Andersson et al 2013), and it is successfully modelled by Hoang et al (2015). Since MAT alignment of irregular shapes is essentially similar to RAT alignment, we predict that pinwheel torques also act to enhance the alignment by lifting the low-J attractor points and create new high-J attractor points.…”
Section: Effect Of Grain Precession Around the Drift Direction Vs Lamentioning
confidence: 70%
“…Hoang & Lazarian (2009b) found that RAT alignment is shown to be enhanced by pinwheel torques. The effect of alignment by H 2 torques is observed in reflection nebula IC 63 (Andersson et al 2013), and it is successfully modelled by Hoang et al (2015). Since MAT alignment of irregular shapes is essentially similar to RAT alignment, we predict that pinwheel torques also act to enhance the alignment by lifting the low-J attractor points and create new high-J attractor points.…”
Section: Effect Of Grain Precession Around the Drift Direction Vs Lamentioning
confidence: 70%
“…First of all, it was found that the alignment can be enhanced in the presence of H 2 torques (Andersson et al 2013;Hoang et al 2015). This does not contradict to MRAT process, as the effect of H 2 torques on grain alignment is expected to be still applicable because the small size cut-off will shift to a smaller size due to H 2 torques, allowing more grains to be aligned and thus increasing the total polarization.…”
Section: Implication For Observations In the Diffuse Mediummentioning
confidence: 99%
“…The grains outside this parameter space were found to be aligned at the low-J attractor point and were shown to be not perfectly aligned. For this generic feature, the degree of radiative alignment can be modeled by a parameter f hithe fraction of grains aligned at high-J attractor points, which allows quantitative predictions of the polarization by RAT alignment for various astrophysical conditions Hoang et al (2015). Observational evidence for RAT alignment is numerous and becomes increasingly available (Andersson & Potter 2007;Whittet et al 2008;Andersson & Potter 2010;Matsumura et al 2011;Andersson et al 2011;Reissl et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The actual mechanism by which the dust grains align with the magnetic field in a manner described above is still unclear (Lazarian, 2007;Andersson et al, 2015). However, radiative torque mechanism, originally proposed by Dolginov & Mitrofanov (1976), seems to be emerging as the most successful one in explaining the dust alignment in various environments (e.g., Hoang & Lazarian, 2014;Hoang et al, 2015;Andersson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%